Fallacy of militant ideology: competing ideologies and conflict among militants, the Muslim world, and the West - Marath, Munir Masood (Religion and international security, 2022)
Nature of conflict -- Heresy of ideas -- Polemics revisited -- Codifications of violence -- Codes of war -- Killing fields -- Fuel of faith : Pakistan - a case study -- Counter narrative.